Self-reported antibiotic stewardship and infection control measures from 57 intensive care units: An international ID-IRI survey. Issue 9 (September 2022) - El-Sokkary, Rehab; Erdem, Hakan; Kullar, Ravina; Pekok, Abdullah Umut; Amer, Fatma; Grgić, Svjetlana; Carevic, Biljana; El-Kholy, Amani; Liskova, Anna; Özdemir, Mehmet; Khan, Ejaz Ahmed; Kizmaz, Yesim Uygun; et al.
Abstract: We explored the self-reported antibiotic stewardship (AS), and infection prevention and control (IPC) activities in intensive care units (ICUs) of different income settings. A cross-sectional study was conducted using an online questionnaire to collect data about IPC and AS measures in participating ICUs. The study participants were Infectious Diseases–International Research Initiative (IDI-IR) members, committed as per their institutional agreement form. We analyzed responses from 57 ICUs in 24 countries (Lower-middle income (LMI), n = 13; Upper-middle income (UMI), n = 33; High-income (HI), n = 11). This represented ( 5%) of centers represented in the ID-IRI. Surveillance programs were implemented in (76.9%−90.9%) of ICUs with fewer contact precaution measures in LMI ones (p = 0.02 ); (LMI:69.2%, UMI:97%, HI:100%). Participation in regional antimicrobial resistance programs was more significantly applied in HI (p = 0.02 ) (LMI:38.4%, UMI:81.8%, HI:72.2%). AS programs are implemented in 77.2% of institutions with AS champions in 66.7%. Infectious diseases physicians and microbiologists are members of many AS teams (59%&50%) respectively. Unqualified healthcare professionals(42.1%), and deficient incentives(28.1%) are the main barriers to implementing AS. We underscore the existing differences in IPC and AS programs' implementation, team composition, and faced barriers. Continuous collaboration and sharing best practices on APM is needed. The role of regional and international organizations should be encouraged. Global support for capacity building of healthcare practitioners is warranted.